2021
DOI: 10.3390/ijerph18189434
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Thyroid Axis

Abstract: Development of obesity is primarily the result of imbalance between energy intake and energy expenditure. Thyroid hormones influence energy expenditure by regulating cellular respiration and thermogenesis and by determining resting metabolic rate. Triiodothyronine influences lipid turnover in adipocytes and impacts appetite regulation through the central nervous system, mainly the hypothalamus. Thyroid-stimulating hormone may also influence thermogenesis, suppress appetite and regulate lipid storage through li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 137 publications
(241 reference statements)
1
60
0
6
Order By: Relevance
“…Obese people with a normal thyroid gland tend to have higher serum TSH and thyroid hormones in serum due to the activation of hypothalamic-pituitary-thyroid axis. 24 In the present study, the mean TSH value was found to be statistically significantly higher in overweight/ obese participants (p=0.02). On the other hand, lipid and glycemic parameters were significantly different in overweight/obese group as expected since their relationships with BMI and obesity are well-known.…”
Section: Discussionsupporting
confidence: 46%
“…Obese people with a normal thyroid gland tend to have higher serum TSH and thyroid hormones in serum due to the activation of hypothalamic-pituitary-thyroid axis. 24 In the present study, the mean TSH value was found to be statistically significantly higher in overweight/ obese participants (p=0.02). On the other hand, lipid and glycemic parameters were significantly different in overweight/obese group as expected since their relationships with BMI and obesity are well-known.…”
Section: Discussionsupporting
confidence: 46%
“…Theories had been generated to illustrate the thyroid dysfunction in obese patients [ 33 ]. It was explained upon the level of adipocytokines, mainly leptin, released from the adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, TSH also increase the leptin production which depends on the adiposity mass [ 37 ]. Elevated TSH may also trigger low-grade chronic inflammation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether the altered thyroid function present in obesity is due to the excess adiposity or, alternatively, the decreased thyroid function is the cause of the excess adiposity. The thyroid axis regulates the adipose tissue and the adipose tissue affects the activity of the thyroid axis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%